Here are my hands - Martin, Bill, 1916- (New York : Henry Holt and Company, 1985)
The owner of a human body celebrates it by pointing out various parts and mentioning their functions, from "hand for catching and throwing" to the "skin thta bundles me in."
Keywords: Body, Human -- Fiction; Stories in rhyme